2023
DOI: 10.1210/clinem/dgad432
|View full text |Cite
|
Sign up to set email alerts
|

Higher Myonuclei Density in Muscle Fibers Persists Among Former Users of Anabolic Androgenic Steroids

Abstract: Background and objective No information exists on the long-lasting effects of supraphysiological anabolic androgenic steroids (AAS) usage on the myocellular properties of human skeletal muscle in previous AAS users. We hypothesized former AAS users would demonstrate smaller myonuclei domains (i.e., higher myonuclei density) compared to matched controls. Methods A community-based cross-sectional study in men aged 18-50 years e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…An additional limitation was that our D 2 O integration period was only 24 h, which is just snapshot over a 7-month period. However, this provides strong evidence that the effects of early AAS use are long-lived and are in agreement with the idea of a potential muscle memory mechanism (15,25). Although previous research supports an androgen-induced muscle memory, more work is required to fully understand the mechanisms involved and to develop effective interventions to prevent or treat age-related declines in protein synthesis rates.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…An additional limitation was that our D 2 O integration period was only 24 h, which is just snapshot over a 7-month period. However, this provides strong evidence that the effects of early AAS use are long-lived and are in agreement with the idea of a potential muscle memory mechanism (15,25). Although previous research supports an androgen-induced muscle memory, more work is required to fully understand the mechanisms involved and to develop effective interventions to prevent or treat age-related declines in protein synthesis rates.…”
Section: Discussionsupporting
confidence: 85%
“…Previous work has demonstrated that brief exposure to androgens has a lasting effect on muscle size and myonuclear number resulting in a higher myonuclei density (15). Recent work observed similar findings in humans (25) whereby former AAS users have an increased transcriptional capacity as represented by a higher myonuclei density and DNA-to-cytoplasm ratio. The increased capacity for mRNA transcription provides a plausible rationale for our observed effects of ND increasing muscle protein synthesis long after cessation of use.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This persistence may be linked to the concept of “muscle memory,” wherein the muscle remains hypertrophied or retains the ability to hypertrophy rapidly for years, even after serum testosterone levels have returned to normal 38 . Muscle biopsies from the vastus lateralis muscle demonstrated persistently elevated myonuclei density and DNA to cytoplasm ratio 4 years after discontinuing the use of AAS 39 . A potential pathway involving irreversible epigenetic methylation, which could be mediated by ARs, has been under investigation, although conclusive evidence is still lacking 40–42 …”
Section: Discussionmentioning
confidence: 99%
“…38 Muscle biopsies from the vastus lateralis muscle demonstrated persistently elevated myonuclei density and DNA to cytoplasm ratio 4 years after discontinuing the use of AAS. 39 A potential pathway involving irreversible epigenetic methylation, which could be mediated by ARs, has been under investigation, although conclusive evidence is still lacking. [40][41][42] Despite ARs were found in the LP, there was no effect of testosterone on HA concentration.…”
Section: Discussionmentioning
confidence: 99%